The Duality of Social Media in Tourism - Irina Maiorescu; Razvan Dina; Rodica Pamfilie; Daniel Zgura (Amfiteatru Economic Journal, 2014)
Today's technologies offer many opportunities for communication and for developing the social, political and economic environments. Social media is one of the channels highly used for personal and business communication in our informational society. However, the various facets of the social media may not be employed in the same manner for the needs of the individual as they are for the needs of the businesses aiming to develop in the tourism sector. This paper aims to identify which of the social media platforms are appropriate for being used for personal purposes and which are more suitable for developing a business in tourism, amongst the users of social media. The paper bases its conclusions on a survey applied on a sample of Romanian young people (18 – 35 years old) involved in tourism business environment, as according to research in the field such as Lenhart, Purcell, Smith and Zichur (2010) and Cabral (2011) this is the most active segment in social media. The findings presented in the paper result from the analysis of the survey responses and they indicate that all four types of social media platforms taken into account: social networks, blogs, micro-blogs and video file sharing platforms are used for both personal and business purposes. However, inside each of the four types of platforms surveyed there were noticed certain preferences, from the point of view of users' interests in communication: personal purpose communication or business in tourism purpose communication.
Keywords: L14; L17; L22; L83; L86; 330; social media; business in tourism; communication; social networks; video file